POLIGAMI DALAM HUKUM AGAMA DAN NEGARA - Muhammad Arif Mustofa (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2017)
Abstract: Marriage in Islam there is a monogomi bersiasfat or one wife and there is also a polygamy that is more than one wife. Polygamy is indeed permissible in Islam but with conditions as a condition to be met. Not only Islam, the State also affirmed the practice of polygamy but still accompanied degan terms that are not much different from the rules of religion. Therefore, if there is someone who wishes to do polygamy then he must understand the rules in religion and the State so recorded also by the State. Polygamy exemplified in Islam needs to be understood not solely to meet biological needs alone. History records, even the practice of polygamy is done more to protect against women at that time. Many women are left to die by their husbands in battle and need protection. The Prophet even practiced polygamy in addition to protecting women also because of the command of Allah. From here, it appears the writer’s desire to raise the theme of polygamy from the point of religion and the State so that it is not misunderstood and used as a shield and a reason for people who are polygamous.Keywords: Polygamy, country and religio